3D Modelling of Outer Surface of Moulded Bra Cup (Journal of Fiber Bioengineering and Informatics, 2018)
Based on the theory of forward engineering design, this paper deals with modelling the outer surface ofmoulded bra cup by using the methods of body measurement, data analysis and 3D modelling. In thestudy, thirty female college students who are 18-24 years old, born and grew up in the northwestern partof China were measured. On the basis of these body measurement data, the features of the human body,the relationship between the basic features of the breast form and the major detail size were analyzed.This is so that the relevant parameters of the chest which is used to describe the perfect female breastshape can be quantified. At the same time, these quantitative parameters were used in the modellingof the outer surface of moulded bra cup to obtain the bra cup which can correct, modify and beautifythe breast shape. It has been demonstrated that the theory of forward engineering design is reasonableand possible to be implemented in the design of moulded bra cup, and in the 3D modelling of the outersurface of moulded bra cup the methods of line-face and face-face should be combined together to makethe process of 3D modeling more effective.